My Thing Is Dead: Experience of Dealing with Diabetic Erectile Dysfunction of Northern Thai Men - Thongtang, Pulawit; Fongkaew, Warunee; Sansiriphun, Nantaporn; Chaloumsuk, Nonglak (Pacific Rim International Journal of Nursing Research, 2021)
Diabetic erectile dysfunction is a common complication affecting men who are living with diabetes mellitus. However, there is a lack of understanding of the experience of men in dealing with this condition in Thailand. This qualitative descriptive study explored the experiences of 15 Thai men in dealing with diabetic erectile dysfunction. They were receiving care in a northern Thailand hospital and were chosen purposefully. In-depth interviews were conducted between December 2016 and December 2017. All interviews were transcribed verbatim and data were analyzed using a thematic analysis approach. Five themes emerged regarding the participants dealing with their condition: Loss of manhood; Embarrassing to disclose; A little relief from medicines; Trying to please a partner, and Getting over it and acceptin. Losing of erectile function caused some men to lose their strength and confidence. They tried different ways to gain an erection to please their partner. However, they had little success in restoring their erectile ability. Some of them learnt to live with their condition. The findings highlight the need to create a supportive environment to encourage men’s self–disclosure and decrease embarrassment. Nurses can design a program for addressing and helping men get over an erectile dysfunction due to diabetes. An essential recommendation is to assess and care for sexual problems as part of routine care for men with diabetes.